MEMBANGUN BENTENG KARAKTER DI ERA DIGITAL: SINERGI PENDIDIKAN KELUARGA, LITERASI DIGITAL ORANG TUA, DAN PEMBENTUKAN MORAL ANAK USIA SEKOLAH - Zulvia Trinova; Syamsuar Hamka; Prisca Diantra Sampe (CV. Lafadz Jaya, 2026)
The digital age has fundamentally transformed the patterns of interaction, learning and values formation amongst Indonesia’s younger generation, whilst also having serious consequences for the erosion of children’s character and moral values. This article aims to analyse the role of family education and parental digital literacy in the moral development of school-age children in the digital age. The study employs a literature review using a descriptive qualitative approach. The findings indicate that the family plays a crucial role as the initial foundation for children’s character development through setting a good behavioural example, open communication, and guidance on technology use consistent with an authoritative parenting style. Parents’ digital literacy is a key factor in strengthening children’s character, as parents’ ability to access, analyse, evaluate and use digital information ethically determines the success of monitoring their children’s online activities. Parents with a high level of digital literacy can act as filters, facilitators and role models in the wise use of technology. Effective digital parenting strategies include co-viewing, setting screen time limits, open communication, and continuous education through collaborative programmes between families, schools and the government. The integration of family education and parental digital literacy creates a safe and educational digital ecosystem for the moral development of school-age children, with religious values, responsibility, empathy and digital ethics as the main pillars.